An exploration of disclosure and non-disclosure patterns in HIV-infected children in Cape Town, South Africa - Shea, Robert F (Adolescent Health Research Institute, 2019)
A cross-sectional, descriptive study combining with open-ended (qualitative) interview questions with quantitative component was conducted to explore disclosure experiences of mothers and caregivers of HIV-infected children. The study was conducted with 102 parents and caregivers at a tertiary hospital in Cape Town delivering care to 303 HIV-infected paediatric patients. The study sample included 102 participants, ranging in age from 16 years to 71 years. The sample included 73 mothers (72%), six fathers (6%), 11 foster-mothers (11%), and 12 caregivers or grandmothers (12%). The median age of participants’ children was 4 (IQR 2-8) years and ranged from five months to 16 years. Only 48 (47%) were old enough for disclosure to be possible. Disclosure or disclosure delay was associated with several factors, including the child’s age or ability to understand, anxiety and guilt about being blamed for infecting the child, fear of exposing the child to stigma, discrimination and social exclusion related to the child disclosing to others, and the hope that the child would be adherent if they understood their illness and the way in which the medication could improve their health outcomes. Only 16 (33%) of 48 participants actually disclosed the child’s HIV status. The results indicate that HIV-disclosure remains a challenging, emotionally-charged experience for mothers and caregivers. The findings of this research, and similar studies, point to the value of integrating disclosure support and planning into routine care for children and adolescents, as well as their parents and caregivers.